The effect of dividend policy and net income on stock prices of companies listed on the indonesia stock exchange For the period 2021-2023 - Rudy Hedianton Saragih; Gamliela Shaina Korompis; Bertha Elvy Napitupulu; Kuncu Saragih; Oktavia Marpaung; Luky Yunia Wennadi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Number of companies listed on the Indonesia Stock Exchange are increasing. These companies have gone public, they issue shares and trade them on the Indonesia Stock Exchange. This provides an option for investors to invest. Before investing, investors analyze published information, so that they can correctly decide which shares to buy. The information analyzed is information about the company's performance, including the company's dividend policy and net profit. Dividend policy is information for investors about the company's performance which is expected to encourage stock prices. The company's net profit shows the performance and ability of the entity to make a profit. Investors will receive large dividends if the company has a large net profit. Investors will be more interested in investing which will result in an increase in stock prices. This study aims to determine the effect of dividend policy and net income on stock prices in companies listed on the Indonesia Stock Exchange in the 2021-2023 period. The population of this study are companies listed on the Indonesia Stock Exchange for the period 2021-2023. With the non-probability sampling technique purposive sampling, 23 companies were selected as samples, so that the amount of data used was 69 data. Data analysis uses multiple linear regression and correlation analysis. The results showed that dividend policy has a positive and significant effect on the stock price of companies listed on the Indonesia Stock Exchange for the period 2021-2023.